Impact of crystalline defects in 4H-SiC epitaxial layers on the electrical characteristics and blocking capability of SiC power devices - Kodolitsch, Elisabeth; Sodan, Vice; Krieger, Michael; Weber, Heiko B.; Tsavdaris, Nikolaos (Materials Research Express, 2022)
In this study, we report the impact of structural 4H-SiC epitaxial defects on the electrical characteristics and blocking capabilities of SiC power devices. The detection and classification of the various crystal defects existing in 4H-SiC epitaxial layers and substrates was carried out with a commercial inspection tool using an optical microscope with a photoluminescence channel (PL). After the fabrication of dedicated test structures, devices that contain a single crystal defect were selected and electrically tested in reverse bias mode. Photon emission microscopy was performed to enable the localization of the leakage current spots within the devices. Thus, a direct correlation of the various crystal defects with the reduced blocking capability mechanism was made. This evaluation helps to set directions and build a strategy towards the reduction of critical defects in order to improve the performance of SiC devices for high power application